2021
DOI: 10.1371/journal.pone.0247454
|View full text |Cite
|
Sign up to set email alerts
|

Let’s (not) get together! The role of social norms on social distancing during COVID-19

Abstract: While effective preventive measures against COVID-19 are now widely known, many individuals fail to adopt them. This article provides experimental evidence about one potentially important driver of compliance with social distancing: social norms. We asked each of 23,000 survey respondents in Mexico to predict how a fictional person would behave when faced with the choice about whether or not to attend a friend’s birthday gathering. Every respondent was randomly assigned to one of four social norms conditions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 39 publications
(59 reference statements)
1
35
0
1
Order By: Relevance
“…The literature distinguishes two main types of social norms: while “descriptive” norms refer to the observed behaviour of others, “injunctive” norms capture the expected moral approval of other people [ 29 ]. Jointly, both forms of social norms foster adherence to preventive behaviour in the context of COVID-19 [ 30 , 31 ], as people may engage in preventive behaviour not because of their belief in the benefit of the behaviour itself, but because they care about their social relations and their reputation in the social environment [ 32 36 ]. In line with these expectations, empirical evidence regarding COVID-19 suggests that people who engage in preventive behaviour are perceived as more prosocial [ 37 ] and express less positive attitudes towards those not wearing masks [ 9 ].…”
Section: Primary Predictors Of Preventive Behaviourmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature distinguishes two main types of social norms: while “descriptive” norms refer to the observed behaviour of others, “injunctive” norms capture the expected moral approval of other people [ 29 ]. Jointly, both forms of social norms foster adherence to preventive behaviour in the context of COVID-19 [ 30 , 31 ], as people may engage in preventive behaviour not because of their belief in the benefit of the behaviour itself, but because they care about their social relations and their reputation in the social environment [ 32 36 ]. In line with these expectations, empirical evidence regarding COVID-19 suggests that people who engage in preventive behaviour are perceived as more prosocial [ 37 ] and express less positive attitudes towards those not wearing masks [ 9 ].…”
Section: Primary Predictors Of Preventive Behaviourmentioning
confidence: 99%
“…Previous empirical studies with respect to COVID-19 have reported puzzling results regarding the effects of social norms and political trust on preventive behaviour. While some studies, using data from the first surge of infections in early 2020, suggest that perceived health risks are the single most important factor in facilitating preventive behaviour [ 20 , 21 ], other studies have highlighted the importance of other factors like political trust and social norms [ 9 , 30 32 ]. We argue that accounting for the intervening factor of perceived health risks might explain these disparate findings, meaning that elevated perceptions of individual health risks (as reported in many countries at the beginning of the pandemic) should reduce the effects of trust and social norms on preventive behaviour because these social mechanisms are more relevant when health risk perceptions are low and thus do not induce people to take preventive measures out of self-interest.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The survey was approved by the IRB of the Instituto Tecnológico Autónomo de México (ITAM) on July 1, 2020, under the name "Social and Behavioral Drivers of Individual Compliance with Preventive Measures during the COVID-19 Epidemic in Mexico" (memorandum letter of approval available upon request from the authors.) In the same survey, we also included the survey experiment described and analyzed in Martínez et al, (2021) [43]. Therefore, recruitment methods and sample description are the same for both articles.…”
Section: Participant Recruitment and Datamentioning
confidence: 99%
“…We conducted a survey experiment embedded within a larger survey focusing on COVID-19 experiences, attitudes, and behaviors. In the same survey, we also included the survey experiment described and analyzed in Martínez et al (2021). Therefore, recruitment methods and sample description are the same for both articles.…”
Section: Participant Recruitment and Datamentioning
confidence: 99%